Soft impact responses of laminated glass simulated with the combined finite-discrete element method. Issue 3 (8th May 2018) - Chen, Xudong; Chan, Andrew
Abstract : Purpose: This paper aims to investigate the responses of laminated glass under soft body impact, including elastic impact and fracture/fragmentation consideration. Design/methodology/approach: The simulation uses the combined finite-discrete element method (FDEM) which combines finite element mesh into discrete elements, enabling the accurate prediction of contact force and deformation. Material rupture is modelled with a cohesive fracture criterion, evaluating the process from continua to discontinua. Findings: Responses of laminated glass under soft impact (both elastic and fracture) agree well with known data. Crack initiation time in laminated glass increases with the increase of the outside glass thickness. With the increase of Eprojectile, failure mode is changing from flexural to shear, and damage tends to propagate longitudinally when the contact surface increases. Results show that the FDEM is capable of modelling soft impact behaviour of laminated glass successfully. Research limitations/implications: The work is done in 2D, and it will not represent fully the 3D mechanisms. Originality/value: Elastic and fracture behaviour of laminated glass under soft impact is simulated using the 2D FDEM. Limited work has been done on soft impact of laminated glass with FDEM, and special research endeavours are warranted. Benchmark examples and discussions are provided for future research.